Influence of Gd alloying and ultrasonic vibration hybrid treatment on the microstructures, mechanical properties and strengthening mechanisms of Al/Mg interface by compound casting - Qingqing Li; Wenming Jiang; Yuancai Xu; Linghui Yu; Ziwei Peng; Yunchang Xin; Zitian Fan (Journal of Materials Research and Technology)
The hybrid treatment of Gd alloying and ultrasonic vibration was employed to improve microstructure and bonding performance of Al/Mg interface by compound casting, and the interfacial microstructures, mechanical properties and strengthening mechanisms of the Al/Mg interface with the hybrid treatment were investigated. It was found that the oxide film between the Al–Mg intermetallic compounds (IMCs) layer and the eutectic layer of the Al/Mg interface with 0.6 wt% Gd was partially dissolved and become less continuous. The Al2Gd and Al8Mn4Gd precipitates were formed and aggregated at the eutectic layer of the interface. The oxide film of the interface with hybrid treatment was completely removed. A more homogeneous interfacial structure was achieved. The Mg2Si particles, Al2Gd and Al8Mn4Gd precipitates were dispersed and refined. The coherent relationships among Mg2Si, Al12Mg17 and δ-Mg as well as the Gd contained precipitates and Al12Mg17 were revealed. The microhardness of the Al/Mg interface with hybrid treatment was the most homogeneous. The shear strength of Al/Mg bimetal with hybrid treatment was 59.0 MPa, which increased by 57.8%, compared with that of the untreated bimetal. The crack origin during shear deformation was changed from the location of oxide film to the boundary between the solid insert and the IMCs layer. The strengthening mechanisms of the Al/Mg interface with hybrid treatment were precipitation strengthening, dispersing strengthening and refinement strengthening.